1978
DOI: 10.1107/s0021889878012844
|View full text |Cite
|
Sign up to set email alerts
|

Scherrer after sixty years: A survey and some new results in the determination of crystallite size

Abstract: Existing knowledge about Scherrer constants is reviewed and a summary is given of the interpretation of the broadening arising from small crystallites. Early work involving the half‐width as a measure of breadth has been completed and Scherrer constants of simple regular shapes have been determined for all low‐angle reflections (h2 + k2 + l2≤ 100) for four measures of breadth. The systematic variation of Scherrer constant with hkl is discussed and a convenient representation in the form of contour maps is appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

72
1,635
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,268 publications
(1,717 citation statements)
references
References 9 publications
72
1,635
0
10
Order By: Relevance
“…It is also interesting to emphasize that, according to the materials obtained and the methodology employed in this paper, an increase in crystallite size also resulted in an increase in specific surface area. In this case, it was confirmed that, in fact, "crystallite size" is not a synonymous for "particle size", as it is emphasized by other authors 45,48 , once that the individual particles may contain several crystallites 41 . In addition, it is well known that the specific surface area and particle size values have an inverse relation to each other, which can be represented by Eq.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…It is also interesting to emphasize that, according to the materials obtained and the methodology employed in this paper, an increase in crystallite size also resulted in an increase in specific surface area. In this case, it was confirmed that, in fact, "crystallite size" is not a synonymous for "particle size", as it is emphasized by other authors 45,48 , once that the individual particles may contain several crystallites 41 . In addition, it is well known that the specific surface area and particle size values have an inverse relation to each other, which can be represented by Eq.…”
Section: Resultssupporting
confidence: 66%
“…The average crystallite size of the solids was estimated from the X-ray patterns, using the Scherrer equation and applying the integral width method, defined as the total area under the maximum diffraction peak divided by the peak intensity 45 . The diffraction peak that was considered in the calculations was the one corresponding to the plane (311), which occurs at 2θ = 36.8.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the reflections from the (110) h square basal planes of AuSSs are barely observable because of the ultrathin nature of the AuSSs. The 2.4-nm dimension, normal to the (110) h plane, results in a weak and broad reflection peak based on Sherrer's theory 19 , whereas the fcc Au nanoparticles, which are 10-25 nm in diameter, produce strong reflections. For comparison, a concentrated solution (similar to a paste) of AuSSs was deposited on a glass slide, so that the AuSSs did not show the preferred orientation.…”
Section: Synthesis and Characterization Of Ausssmentioning
confidence: 99%
“…at half-maximum (fwhm; β value in the equation) of their corresponding XRD peaks: 47,48 where τ is the size of the NP, λ is the X-ray wavelength, and k is a constant. 31,32 The size of the metallic AgNP in the [CEL+KER+Ag 0 ] composite was found to be 9 ± 1 nm, while the AgClNP in the [CEL+KER+Ag + ] composite has a size of 27 ± 2 nm.…”
mentioning
confidence: 99%